COMPARISON OF UNTRANSLATABLE WORDS IN UZBEK, RUSSIAN AND ENGLISH (BASED ON “SHUM BOLA” GAFUR GULOM) - Alimova, Munisa (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article examines the issues of untranslatable words within the context of modern translation theory. In the first section of analyzes how this phenomenon has been studied and developed in Russia, in the United States and Uzbekistan with a focus on the formation of different approaches to understanding untranslatability and its role in language. Then explores the translation challenges that arise when conveying culturally specific vocabulary. It proposes a classification of untranslatable words into thematic groups (such as vocabulary related to food, clothes and others), also analyzes the most effective strategies for translating them, taking into account context and communicative purpose. In the practical section will be given some examples from the Uzbek book “Shum bola”, comparing the original text with English translation. The analysis of specific examples makes it possible to identify the singularity of translation cultural words and to determine how accurately they are conveyed in translation. As a result, the study helps to identify translation approaches and demonstrates the importance of cultural context in choosing translation methods.